The effectiveness of project-based learning by using Canva application on students’ descriptive writing achievement - Ruswandi, Riki; Gumelar, Wahyu Satya; Ermaya, Annisa Salsabila; Ginanjar, Gigin (Universitas Islam Sultan Agung, 2024)
As one of English basic skills, writing is considered the most difficult skill for students, such as arranging correct sentences, writing the topic sentence, organizing ideas, and lack of vocabulary. Therefore, an appropriate learning model and media that support understanding and development of writing skills can help students to increase their writing ability. This study aims to examine the effectiveness of using Project-Based Learning through the Canva application to improve students’ writing achievement in describing historical and tourism places as one of the basic competencies that students should master at the senior high school level. This study aimed to find out whether Project-Based Learning and the Canva application influence students’ writing and to analyze the development of students’ writing after implementing PjBL by making written text using the Canva application. The writers used a quantitative method which is a quasi-experimental research design by applying a non-equivalent pre-test post-test control group design. The data were obtained through the writing test in collecting students’ scores. To analyze the data, the writer used a t-test with a significant level of 0.05. The samples were two classes in the tenth grade of SMA Karya Pembangunan Cicalengka which consisted of 66 students. Based on the research analysis, students’ average score on the pre-test was 55.3 and students’ average score on the post-test was 75.37. The result also showed that ttable was 1.669 and tvalue was 2.924, which means that ttable was higher thantvalue at significant level 5%. It indicated thatH0 is rejected and Ha is accepted. Based on the result of t-test calculation, it can be stated that the use of PjBL through Canva application is effective to facilitate students in improving students’ learning achievement, especially in writing descriptive text about historical and tourism places.